Functional social structure in baboons: Modeling interactions between social and environmental structure in group-level foraging. Issue 126 (January 2019) - Bonnell, Tyler R.; Henzi, S. Peter; Barrett, Louise
Abstract: In mobile social groups, cohesion is thought to be driven by patterns of attraction at both the individual and group level. In long-lived species with high group stability and repeated interactions, such as baboons, individual-to-individual attractions have the potential to play a large role in group cohesion and overall movement patterns. In previous work, we found that the patterning of inter-individual attraction gave rise to an emergent group-level structure, whereby a core of more influential, inter-dependent individuals exerted a unidirectional influence on the movements of peripheral animals. Here, we use agent-based modeling of baboon groups to investigate whether this core–periphery structure has any functional consequences for foraging behavior. By varying individual level attractions, we produced baboon groups that contained influence structures that varied from more to less centralized. Our results suggest that varying centrality affects both the ability of the group to detect resource structure in the environment, as well as the ability of the group to exploit these resources. Our models predict that foraging groups with more centralized social structures will show a reduction in detection and an increase in exploitation of resources in their environment, and will produce more extreme foraging outcomes. More generally, our results highlight how a group's internal social structure can result in mobile social animals being able to more (or less) effectively exploit environmental structure, and capitalize on the distribution of resources. In addition, our agent-based model can be used to generate testable predictions that can be tested among the extant baboon allotaxa. This will add value to the existing body of work on responses to local ecology, as well as providing a means to test hypotheses relating to the phylogeography of the baboons and, by analogy, shed light on patterns of hominin evolution in time and space.